Clinical, epidemiological and autoimmune associations in childhood vitiligo in Qatar - Al Mannai, Haya; Allam, Mohamed; Riad, Hassan (International Journal of Research in Dermatology, 2020)
Background: Childhood vitiligo although clinically similar to adult onset vitiligo but it has distinct clinical, epidemiological and prognostic features compared to adult onset vitiligo. Methods: This is a retrospective study that was carried out on 85 pediatric patients up to age of 18 years old with the diagnosis of vitiligo, where the clinical and epidemiological data including clinical type of vitiligo, family history of autoimmune diseases like thyroid disorders and diabetes mellitus and laboratory results including anti-thyroid peroxidase antibodies (anti-TPO antibodies), anti-parietal cell antibodies, antinuclear antibodies (ANA), Vitamin D and Vitamin B12 were retrieved from the files of these patients. Results: The mean age of the children affected by vitiligo was 10.4 years, the mean age of onset of vitiligo was 5.4 years, 54 (63.5%) percent were girls and 31 (36.5%) were boys. A positive family history of vitiligo was found in 44.7% of the participants, family history of DM was found in 64.7% of patients and family history of thyroid disease was found in 32.9% of the participants. The prevalence of thyroid autoimmunity was found to be in 22.4% of total participants. Conclusions: Childhood vitiligo has distinct clinical features, more common family history for autoimmune diseases and thyroid autoantibodies rather than overt clinical diseases, which raise the necessity to perform a routine initial immunological and thyroid screening in children with vitiligo and to repeat them at annual bases if there were abnormal values at base line or strong family history.